Pengaruh Harga, Iklan, dan Citra Merek (Brand Image) Terhadap Keputusan Pembelian Smartphone Android Samsung Galaxy Series (Studi Kasus Pada Mahasiswa Fakutas Ekonomi dan Bisnis UMS) - Prakoso, Luqman Arif; , Dra. Chuzaimah, M.M (2015)
The development of time and increasing needs of communication causing smartphone business industry more challenging. Samsung is one of companies engaged in electronics production sector one of it's production is smartphone. The number of smartphone industry competition causing increasingly diverse consumer choice. And the factor affecting of consumer opinion to choose smartphone are price factor, advertisement, brand image. The formulation problem in this research is how price, advertisement, and brand image has influence by simultaneous through partial toward purchasing decision of smartphone Samsung Galaxy series in Faculty of Economic and Business Muhammadiyah Surakarta University students. The hypothesis of this research is thought to exist in partial positive influence pricing, advertising, brand image on purchasing decisions. The population of this research is Faculty of Economic and Business Muhammadiyah Surakarta University students by taking 100 respondent as sample. This research using classical assumption test, multiple regression analyst, t test method, f test method, and R2 test method. The result of multiple regression is independent variable has most influence to dependent variable is advertisement (0,345). Result of t-test proved that all of independent variable (price, advertisement, and brand image) has positive influence to dependent variable it is decision purchasing. And the coefficient of determination (adjusted R2) is 37,3% which mean could be interpret that price variable, advertisement, and brand image able to explain to the variation of the variable changes in purchasing decisions by 37,3% while the rest is 62,7% explained by other variable that are not used in this research. That means all hypothesis proven true, the variable pricing, advertisement, and brand image individual positive influence on purchasing decisions. Keyword: price, advertisement, brand image, purchasing decision